2019
DOI: 10.3390/w11071459
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the GPM IMERG v5 and TRMM 3B42 v7 Precipitation Products in the Yangtze River Basin, China

Abstract: The purpose of this study is to quantitatively evaluate the accuracy of the GPM IMERG v5 and the TRMM 3B42 v7, with the reference of 224 rain gauge stations over the Yangtze River basin in China from April 2014 to December 2017. The results showed that: (1) The changing pattern of IMERG v5 was similar to the 3B42 v7, and higher correlations can be found between the satellite-based precipitation products (SPPs) and observed precipitation for the monthly and annual time scale; (2) the IMERG v5 tended to overesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 44 publications
(46 reference statements)
2
24
0
1
Order By: Relevance
“…Each of the three categorical metrics has been sequentially calculated annually for the days when daily rainfall exceeds 1, 5, 10, 25, 50, 75, 100, and 150 mm/d. Similar daily rainfall thresholds have been used in previous studies, such as Wu et al [29], Anjum et al [43], and Tan et al [49].…”
Section: Categorical Evaluation Metrics (1) Temporal Variationmentioning
confidence: 93%
See 1 more Smart Citation
“…Each of the three categorical metrics has been sequentially calculated annually for the days when daily rainfall exceeds 1, 5, 10, 25, 50, 75, 100, and 150 mm/d. Similar daily rainfall thresholds have been used in previous studies, such as Wu et al [29], Anjum et al [43], and Tan et al [49].…”
Section: Categorical Evaluation Metrics (1) Temporal Variationmentioning
confidence: 93%
“…Precipitation in the basin is abundant, but also highly seasonal. Steep slopes combined with ample rainfall in summer have aggravated the risk of natural disasters such as floods and mudslides [29]. The flood in June 2016 in the SRB, for instance, has affected 58,000 people with a direct economic loss of 168 million RMB.…”
Section: Introductionmentioning
confidence: 99%
“…The GPM precipitation algorithm, Integrated Multi-satellite Retrievals for GPM (IMERG), is based upon the experiences from the TRMM algorithm. As the spatiotemporal resolution and coverage of GPM have been extended beyond the TRMM resolution and coverage, the performance of the GPM IMERG products needs to be evaluated and validated globally.Several studies have compared the GPM IMERG and TRMM products with ground-based measurements, i.e., rain gauge and weather radar [4,6,10,[15][16][17][18][19], considering their hydrological applications [14,[20][21][22]. Also, different GPM IMERG products regarding temporal resolutions have been evaluated considering various climatic and topographic conditions using various statistical measures across the world [5,[23][24][25][26][27][28][29][30].…”
mentioning
confidence: 99%
“…The IMERG is the successor of TMPA, and the global products of IMERG have also been evaluated. Some studies have compared GPM and TRMM products [14,[33][34][35][36][37]. For example, Wang et al [38] indicated that IMERG correlates better with observations than TMPA, whereas the bias of IMERG is larger than that of TMPA at multiple temporal and spatial scales over Northeastern Tibetan Plateau.…”
Section: Introductionmentioning
confidence: 99%